Alokasi Kerja Rumah Tangga Petani Kentang di Kecamatan Karangreja Kabupaten Purbalingga - Shabila, Riany Aulia; Sutanto, Agus; Putri, Dindy Darmawati (Universitas Galuh, 2024)
Karangreja District is a potato producing area Potato production in this area is fluctuating caused by labor factors that experience gender gaps. Women workers have minimal access to agricultural resources. This study aims to 1) examine the allocation of work in farmer households potato farming in Karangreja Sub-District, Purbalingga Regency, 2) analyzing the outpouring of farmer household work on potato farming in Karangreja Sub-District, Purbalingga Regency. This research uses a descriptive method which was conducted in Kutabawa Village and Serang Village, Karangreja Sub-District. The sampling was taken by using purposive sampling with a sample of 70 farmers. The research data collection techniques using interviews, questionnaires, document study, and observation. The data analysis technique using Mosher analysis and work outpouring analysis. The results showed that 1) Allocation of household work for potato farmers in Karangreja Sub-District is divided into three, namely productive (farming), reproductive (household) and social. The dominant productive work allocation was carried out by husbands such as activities land preparation, planting, weeding, stake installation, spraying, harvesting and postharvest. The dominant reproductive work allocation was carried out by the wife such as activities cooking, shopping, cleaning the house, washing clothes, taking care of the children. Social allocation dominantly carried out by the wife in recitation activities and helping with celebrations, meanwhile dominant husband in farmer group meeting activities and community service. 2) The total work outpouring of husband amounted to 2,225.93 HOK per planting season per 20,92 Ha, and total work outpouring of wife amounted to .201,29 HOK per 20,92 Ha.